PENGARUH PEOPLE POWER DALAM PERADILAN DI INDONESIA - Saputra, Filip Jaya; Putri, Ollanisa; Sari, Pebri Nopita; Alimni, Alimni; Ismail, Ismail (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: The role of society in law enforcement in this country is very important. This role needs to be supported by discipline in complying with established laws and regulations. This article, which uses a normative legal research methodology, concludes that, in fact, the content of the rule of law applied in Indonesia contains the principle of the dignity of man, which contains the principles of democracy regarding the ideas of constitutionalism and a government that is given limited authority. With the rule of law, justice and people’s welfare can be achieved, because there is the right of the people to participate in voicing justice in accordance with the fifth Pancasila precept which reads “social justice for all Indonesian people”. Keywords: People Power; Justice. Abstrak: Peran masyarakat dalam penegakan hukum di negeri ini sangatlah penting. Peran tersebut perlu ditunjang dengan disiplin dalam mematuhi peraturan perundang-undangan yang sudah ditetapkan. Artikel yang menggunakan metodologi penelitian hukum normatif ini menyimpulkan, sejatinya, isi dari rule of law yang diterapkan di Indonesia mengandung asas dignity of man, yaitu berisi prinsip dari demokrasi mengenai ide-ide konstitualisme beserta pemerintah yang diberi kewenangan terbatas. Dengan adanya rule of law, maka keadilan juga kesejahteraan rakyat bisa tercapai, karena adanya hak dari rakyat untuk ikut serta dalam menyuarakan keadilan sesuai dengan Pancasila sila kelima yang berbunyi “keadilan sosial bagi seluruh rakyat Indonesia”. Kata Kunci: People Power; Peradilan